GEOGRAPHICAL LOCATION AS A MODERATOR IN THE RELATIONSHIP BETWEEN ICT ADOPTION AND MICRO-ENTREPRENEURS’ PERFORMANCE IN MALAYSIA - Nur Hazirah Hamdan; Nur Diyana Mustapha; Shahri Abu Seman (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Micro-entrepreneurs play a pivotal role in the socio-economic development of low-income households, significantly contributing to sustainable economic growth. Acknowledging their financial constraints, Islamic microfinance institutions, such as Amanah Ikhtiar Malaysia (AIM), are essential in providing the financial resources needed for their success. Research indicates that beyond financial support, other resources like the integration of ICT into business processes can accelerate growth. Therefore, this study aimed to examine the impact of ICT adoption on the performance of micro-entrepreneurs, considering the moderating effect of geographical location. The research involved 416 AIM clients from Selangor and Pahang, encompassing both urban and rural areas. Using partial least squares – structural equation modeling (PLS-SEM), the analysis revealed that ICT utilization significantly boosts the performance of micro-entrepreneurs, with geographical location influencing the outcomes differently in urban and rural contexts. These findings offer valuable insights for Islamic microfinance institutions to develop more targeted strategies, such as enhancing infrastructure, increasing ICT awareness, and adapting business models to the digital economy. Furthermore, the study can guide both the government and microfinance institutions in formulating effective support measures for micro-entrepreneurs, tailored to their performance across various locations especially in rural areas.